Superare il guado. Riflessioni su archeologia, storia sociale e modelli di autorappresentazione delle disparità: alcuni esempi dalle comunità antiche e moderne - Acconcia, Valeria (Ex Novo: Journal of Archaeology, 2021)
Starting from personal observations about contemporary expressions of gender / age / status-based exclusion and disparity, the paper aims at synthetizing the most relevant theoretical issues about possible ways of self-representation in “traditional” and ancient societies, through the analysis of case-studies from pre-roman communities in Central Italy, focusing on the role of the individuals, as they emerge mainly from the funerary record. After a brief review of the research history, the paper analyses the differences between the Middle-Thryrrenian peoples (as Etruscans, Faliscans and Latins) and those settled along the Middle-Adriatic coast. The formers are characterized by princely burial habits, which probably reflect the role of exceptionally rich individuals (both males and females); on the other hand, in the “Italic” regions of Abruzzo and Molise, the archaic communities seem to be organized on an egalitarian basis and with a lower visibility for adult women, although this may reflect a “contrastive” intent, emphasizing the differences with the wealthy Tyrrhenian lifestyle. Then, the paper outlines cases of inequality and abuse from the Veneto region and from Etruria and Latium vetus, connecting them also to the phenomenon of ancient and modern slavery and evidencing the impact of individual suffering as a possible incentive towards social change.